2017
DOI: 10.1111/beer.12158
|View full text |Cite
|
Sign up to set email alerts
|

Tracing stakeholder terminology then and now: Convergence and new pathways

Abstract: Over the past four decades, stakeholder research has united a chorus of voices from different disciplines using different terminology for different audiences all related to a seemingly similar topic:those that affect and are affected by business. By juxtaposing a comprehensive review of the early years of stakeholder research against more recent stakeholder research, we identify areas of common convergence (a focus on relationships and Freeman's definition of a stakeholder) as well as emergent scholarship (mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 233 publications
1
25
0
4
Order By: Relevance
“…Using stakeholder theory as an overarching framework (Freeman, Harrison, Wicks, Parmar, & de Colle, ; Griffin, ), several studies have supported that higher levels of PCSR‐fit cause beneficial firm evaluations. The rationale is that PCSR‐fit acts as a cue that attracts stakeholders' attention, especially consumers (Deng & Xu, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Using stakeholder theory as an overarching framework (Freeman, Harrison, Wicks, Parmar, & de Colle, ; Griffin, ), several studies have supported that higher levels of PCSR‐fit cause beneficial firm evaluations. The rationale is that PCSR‐fit acts as a cue that attracts stakeholders' attention, especially consumers (Deng & Xu, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Based on the agency theory, shareholders may demand external mechanisms such as voluntary CSR disclosure (Fernández‐Feijoo et al, ; Jo, Song, & Tsang, ) in order to monitor managers’ functions and obtain greater transparency of financial or nonfinancial information. In this sense, the agency approach assigns the board the traditional role of representing the shareholders and protecting them from managers (Griffin, ). In this regard, board composition has a relevant role in the decision‐making process (Hassan, Miglietta, Paltrinieri, & Floreani, ) since it reduces agency costs and encourages CSR disclosure.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Finally, as different authors have indicated (Griffin, ; Renouard & Ezvan, ), the analysis of how companies become involved in communities to improve human development should be promoted. These works indicate that studies about the community have become increasingly important in recent years, in line with the United Nations goals for Sustainable Development.…”
Section: Conclusion Limitations and Future Research Directionsmentioning
confidence: 99%
“…Finally, as different authors have indicated (Griffin, 2017;Renouard & Ezvan, 2018) The tables with regression analysis and the data used in this paper can be obtained in the following Zenodo community (https://zenodo.org/ communities/ccis/about/).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%